2020
DOI: 10.1371/journal.pone.0229257
|View full text |Cite
|
Sign up to set email alerts
|

Social and clinical predictors of short- and long-term readmission after a severe exacerbation of copd

Abstract: Introduction and objectives The aim of this study was to evaluate the predictive ability of multiple social, and clinical factors for readmission after a severe acute exacerbation of COPD (AECOPD) during various time periods. Methods We performed a prospective cohort study in which recruited patients with AECOPD. We systematically collected numerous clinical (symptoms, pulmonary function, comorbidities, and treatment) and social (financial situation, housing situation, family support, caregiver overload, abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…In our study, dependence to carry out activities may not have been related to caregiver overburden, because the discriminative capacity of these variables was likely much lower in our hands than in previous studies in the same cohort 4,21 or in other studies with larger samples of patients with different profiles. 33 This was because of the specific profile of the COPD patients with a regular informal caregiver that were examined in our work-almost all of which had some degree of dependence, a high frequency of hospitalizations, and a significant need for care.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…In our study, dependence to carry out activities may not have been related to caregiver overburden, because the discriminative capacity of these variables was likely much lower in our hands than in previous studies in the same cohort 4,21 or in other studies with larger samples of patients with different profiles. 33 This was because of the specific profile of the COPD patients with a regular informal caregiver that were examined in our work-almost all of which had some degree of dependence, a high frequency of hospitalizations, and a significant need for care.…”
Section: Discussioncontrasting
confidence: 65%
“…The SocioEPOC Cohort comprised 253 patients; a detailed description and analysis of all the variables collected for these patients has already been published. 6,21 Briefly, 63 (24.9%) of the patients lived alone, 71 patients lived with others, but those household members did not have a caregiver role, and 119 (47%) had a primary caregiver, of which 20 (16.8%) were paid and 99 (83.2%) were informal caregivers. These data are shown in the study flowchart presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, just over 40% of death certificates included COPD as part of the dying process, implying that the real burden of the disease in the mortality statistics is considerably higher. In clinical hospital cohort studies published in Spain, the most frequent causes of mortality reported in patients with COPD are neoplasms and cardiovascular diseases [ 22 , 23 ]. This is in line with our study in that when COPD is not considered to be the underlying cause of death, most of the patients die due to neoplasms (essentially bronchopulmonary), different cardiovascular diseases, or dementias.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in a study in two urban hospitals, which included also non-chronically ill patients, living alone showed no effect on the potentially preventable hospital readmission rate (42). Neither showed living alone and care giver availability as having an effect on the 30-day readmission rate in severe COPD patients when controlling for health status and further social factors (29).…”
Section: Introductionmentioning
confidence: 90%